2017
DOI: 10.3892/mmr.2017.7241
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of rats subjected to water immersion and restraint stress as an insight into gastric ulcers

Abstract: In the present study, comparative proteomic analysis was performed in rats subjected to water immersion-restraint stress (WRS). A total of 26 proteins were differentially expressed and identified using matrix-assisted laser desorption/ionization time of flight mass spectrometry. Among the 26 differentially expressed protein spots identified, 13 proteins were significantly upregulated under WRS, including pyruvate kinase and calreticulin, which may be closely associated with energy metabolism. In addition, 12 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Abnormal regulation of ENS can induce gastrointestinal dysfunction, by elevating the amplitudes and index values of gastric motility (gastric hyperkinesia), decreasing gastric mucosal blood flow (GMBF) and gastric mucus secretion, increasing the production of gastric acid and proliferation of gastric mucosal cells [14,[24][25][26][27] . Huang et al [15][16][17] examined the molecular signaling pathways related to the maintenance of gastrointestinal tract homeostasis and gastric mucosal barrier integrity, as well as the energy-related proteins that retain the levels of intracellular adenosine triphosphate (ATP). However, the exact functions of these molecules in SGML need to be further evaluated using molecular biology techniques.…”
Section: Peripheral Nervous Mechanism Of Rwis-induced Gml Ensmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal regulation of ENS can induce gastrointestinal dysfunction, by elevating the amplitudes and index values of gastric motility (gastric hyperkinesia), decreasing gastric mucosal blood flow (GMBF) and gastric mucus secretion, increasing the production of gastric acid and proliferation of gastric mucosal cells [14,[24][25][26][27] . Huang et al [15][16][17] examined the molecular signaling pathways related to the maintenance of gastrointestinal tract homeostasis and gastric mucosal barrier integrity, as well as the energy-related proteins that retain the levels of intracellular adenosine triphosphate (ATP). However, the exact functions of these molecules in SGML need to be further evaluated using molecular biology techniques.…”
Section: Peripheral Nervous Mechanism Of Rwis-induced Gml Ensmentioning
confidence: 99%
“…The fourth level includes higher brain centers that provide input for integrative functions at level 3 [7,8] . The nervous mechanisms of SGML have been explored by many scholars from all over the world using methods such as basic physiology, electrophysiology, immunocytochemistry and pharmacology on the basis of neurotransmitters (neuromodulators), receptors, agonists and blockers [9][10][11][12][13][14][15][16][17][18] . In this study, the nervous mechanism of restraint water-immersion stress (RWIS)-induced gastric dysfunction was investigated, in order to provide ideas to further reveal the nervous mechanism underlying the occurrence and development of SGML.…”
Section: Introductionmentioning
confidence: 99%
“…Restraint water-immersion stress (RWIS) can cause serious gastrointestinal dysfunction and has been widely used to study the un-derlying molecular mechanisms of stress-induced gastric ulcer (SGU) and to screen potential curative drugs[4,5]. The primary central mechanism through which brainstem circuits regulate gastric function under normal physiological conditions has been fundamentally clarified[6-8], and the peripheral regulatory mechanism of gastric ulcers induced by RWIS has also drawn much attention[9-12]. Previous studies have reported that neuronal hyperactivity of vagal parasympathetic efferents, which mostly originate in the primary gastrointestinal control centre of the central medulla (mainly in the dorsal motor nucleus of the vagus and partly in the nucleus ambiguous) and are further mediated by the higher central-anterior hypothalamus (mainly the paraventricular nucleus and supraoptic nucleus), leads to gastric dysfunction[13-15].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of isobaric tags for relative and absolute quantitation (iTRAQ) with multidimensional liquid chromatography and tandem mass spectrometry (LC–MS/MS) analysis is one of the most sensitive proteomic technologies for detecting and quantitatively analysing low-abundance proteins, and this approach has been widely used to discover disease-specific targets and biomarkers for a variety of diseases[12,38-41]. To the best of our knowledge, an iTRAQ-based approach has been applied to study the central mechanism of gastrointestinal dysfunction induced by RWIS.…”
Section: Introductionmentioning
confidence: 99%